Prevention of Islet Allograft Rejection in Diabetic Mice by Targeting Janus Kinase 3 with 4-(4’-Hydroxyphenyl)-amino-6,7-dimethoxyquinazoline ( JANEX-1) - Cetkovic-Cvrljea, Marina; Dragt, Angela L.; Uckuna, Fatih M. (Arzneimittelforschung, 2003)
Janus kinase (JAK) 3-deficient mice were not able to reject allogeneic islet allografts. The JAK3 inhibitor 4-(4’-hydroxyphenyl)-amino-6,7-dimethoxyquinazoline (CAS 202475-60-3, JANEX-1, WHI-P131) prevented the rejection of islet allo-grafts in mice with a normal JAK3 expression status. The combination of JANEX-1 and cyclosporin A (CAS 59865-13-3) was more effective than either agent alone.
Keywords: Diabetes, mouse, type 1; 4-(4’-Hydroxyphenyl)-amino-6,7-dimethoxyquinazoline; Islet allogeneic transplantation, allograft rejection; JANEX-1; Janus kinase 3; Protein tyrosine kinase, mouse; WHI-P131